2012
DOI: 10.1021/jp308212h
|View full text |Cite
|
Sign up to set email alerts
|

New Implicit Solvation Scheme for Solid Surfaces

Abstract: It is shown that the effect of water on the bonding characteristics of transition metal surfaces with adsorbates is short-ranged. As a result, adsorption energies in water can be evaluated by a combination of plane-wave density functional theory calculations in vacuum and properly chosen cluster model calculations with and without an implicit solvation model. The scheme is demonstrated for a model C−C cleavage reaction on Pt (111) and for predicting CO frequency shifts on Pd and Pt due to water. We conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 49 publications
0
65
0
1
Order By: Relevance
“…Moreover, Heyden et al have proposed a simple but highly efficient approach for modeling reactions at solid–liquid interfaces with implicit solvation models, by which they found that water can stabilize the dehydrogenated derivatives of propionic acid and propionate and thus affect the reaction mechanism of propanoic acid hydrodeoxygenation over a model Pd(211) catalyst …”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…Moreover, Heyden et al have proposed a simple but highly efficient approach for modeling reactions at solid–liquid interfaces with implicit solvation models, by which they found that water can stabilize the dehydrogenated derivatives of propionic acid and propionate and thus affect the reaction mechanism of propanoic acid hydrodeoxygenation over a model Pd(211) catalyst …”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…12 In their implicit solvation model for surfaces (iSMS), reaction energies are computed with DFT applying periodic boundary conditions and solvation effects are estimated separately on large metallic clusters using a polarizable continuum model (PCM) for the solvent description. 12 PCM, which accounts for the electrostatic interaction between the solute and the solvent, is well-established in molecular chemistry 13 but less common for metal/liquid interfaces 14,15 since it has only recently become available to the public for periodic boundary conditions. 16 PCM can not describe any direct solvent effects and might be inaccurate for specific hydrogen bonds, 17 which makes the combination of micro-solvation with PCM particularly attractive.…”
Section: Introductionmentioning
confidence: 99%
“…23 Therefore, different approximations have been proposed: inclusion of only a couple of solvent molecules (called micro-solvation) 24,25 , adsorption of ice-like water layers on metallic surfaces 26,27 , the use of a combination of optimization and AIMD, 11,18,19 the classical treatment of solvent interactions 16,28 or the application of implicit solvent models. [29][30][31] In terms of accessible and interpretable differences between gas-phase and solution-phase reactivity, the advantage of implicit solvents is that solvation energies are directly accessible, which is not the case for AIMD simulations. On the other hand, the main limitation of implicit solvents is that no direct participation of the solvent can be described, in contrast to micro-solvation approaches.…”
Section: Introductionmentioning
confidence: 99%